2016
DOI: 10.1007/s10534-016-9932-6
|View full text |Cite
|
Sign up to set email alerts
|

Leaf proteome characterization in the context of physiological and morphological changes in response to copper stress in sorghum

Abstract: Copper (Cu) is an essential micronutrient required for normal growth and development of plants; however, at elevated concentrations in soil, copper is also generally considered to be one of the most toxic metals to plant cells due to its inhibitory effects against many physiological and biochemical processes. In spite of its potential physiological and economical significance, molecular mechanisms under Cu stress has so far been grossly overlooked in sorghum. To explore the molecular alterations that occur in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 88 publications
(114 reference statements)
1
14
0
Order By: Relevance
“…They concluded that protein secretion is a major response of sorghum to osmotic stress [34]. Another study of sorghum also used physiological and comparative proteomics to study abiotic stress response and to identify protein groups responding to drought, salinity, and Cd/Cu stress in sorghum [35][36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that protein secretion is a major response of sorghum to osmotic stress [34]. Another study of sorghum also used physiological and comparative proteomics to study abiotic stress response and to identify protein groups responding to drought, salinity, and Cd/Cu stress in sorghum [35][36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…Most reports, however, have focused on herbaceous plants, including rice [17][18][19], Allium cepa [20], Oenothera glazioviana [21], Arabidopsis [22], Cannabis sativa [23], Agrostis capillaris [24], Elsholtzia splendens [25,26], sorghum [27,28] and wheat [29], while only one study investigated Cu-toxic effects on protein profiles in leaves of woody plant Eucalyptus camaldulensis [30]. Also, most of the above studies mainly focused on Cu-toxicity-responsive proteins occurring in roots because Cu is preferentially accumulated in Cu-stressed roots, while only few studies investigated Cu-toxic effects on protein profiles in leaves [25,27,29,30]. Evidence shows that the toxic effects of Cu on plant proteomics vary with Cu concentration, plant species, populations and/or cultivars, and plant tissues [17,18,24,25,[27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Also, most of the above studies mainly focused on Cu-toxicity-responsive proteins occurring in roots because Cu is preferentially accumulated in Cu-stressed roots, while only few studies investigated Cu-toxic effects on protein profiles in leaves [25,27,29,30]. Evidence shows that the toxic effects of Cu on plant proteomics vary with Cu concentration, plant species, populations and/or cultivars, and plant tissues [17,18,24,25,[27][28][29]. Therefore, more extensive proteomic research on the leaves of woody plants is needed to elucidate the molecular mechanisms of plants under Cu-toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Protein extraction from the 10-LS and FS leaves of the sesame seedling was performed using the trichloroacetoc acid / acetone precipitation method as described Roy et al (2016). About 500 mg of the frozen leaf tissue was ground into a fine powder in liquid nitrogen.…”
Section: Determination Of Plant Height Stem Diameter and Leaf Chlormentioning
confidence: 99%